2020
DOI: 10.1371/journal.pone.0230267
|View full text |Cite
|
Sign up to set email alerts
|

Topical dual-probe staining using quantum dot-labeled antibodies for identifying tumor biomarkers in fresh specimens

Abstract: Rapid, intra-operative identification of tumor tissue in the margins of excised specimens has become an important focus in the pursuit of reducing re-excision rates, especially for breast conserving surgery. Dual-probe difference specimen imaging (DDSI) is an emerging approach that uses the difference in uptake/clearance kinetics between a pair of fluorescently-labeled stains, one targeted to a biomarker-of-interest and the other an untargeted isotype, to reveal receptor-specific images of the specimen. Previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…PAI was created for quantitative in vivo imaging, where non-specific accumulation of protein-based, radiolabeled affinity reagents dominated malignant tissue signals but could be corrected for by normalizing the targeted signal to the signal of a co-administered, control antibody labeled with an isotope of different energy [40]. In this reinvigorated technique, spectrally-distinct targeted and untargeted imaging probes are used to correct for non-specific uptake to quantify drug target availability (DTA; also termed "binding potential") [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. We have expanded the PAI technique to measure intracellular targets with the use of spectrally-distinct, fluorescently-labeled targeted and untargeted drug derivatives, such as TKIs [58].…”
Section: Introductionmentioning
confidence: 99%
“…PAI was created for quantitative in vivo imaging, where non-specific accumulation of protein-based, radiolabeled affinity reagents dominated malignant tissue signals but could be corrected for by normalizing the targeted signal to the signal of a co-administered, control antibody labeled with an isotope of different energy [40]. In this reinvigorated technique, spectrally-distinct targeted and untargeted imaging probes are used to correct for non-specific uptake to quantify drug target availability (DTA; also termed "binding potential") [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. We have expanded the PAI technique to measure intracellular targets with the use of spectrally-distinct, fluorescently-labeled targeted and untargeted drug derivatives, such as TKIs [58].…”
Section: Introductionmentioning
confidence: 99%
“…A robust DDSI protocol with high sensitivity and specificity for differentiation between benign and malignant breast tissues 36 , 37 , 42 44 was previously developed and optimized using antibody-based probes on resected specimens to a total staining and imaging time of 8 min for routine intraoperative use with minimal disruption to the clinical workflow. With advancements in FGS technologies and increasing clinical adoption, the overall goal of this study was to expand the DDSI tumor margin assessment methodology to other cancer types, where prostate cancer was evaluated herein.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple groups have shown that including a spectrally distinct non-targeted isotype probe in the staining solution, acquiring images of both probes in separate channels, and mathematically comparing the two channels helps compensate for imaging system inhomogeneity and produce images of receptor-specific tumor contrast [ 27 , 28 , 35 – 39 ]. This strategy, termed dual-probe difference specimen imaging (DDSI) in our lab, has been applied using antibodies labeled with surface-enhanced Raman scattering (SERS) nanoparticles [ 26 28 ], quantum dots [ 40 ] or with spectrally distinct fluorophores [ 35 37 ] to target various biomarkers, including ERBB1 (EGFR), ERBB2 (HER2), estrogen receptor, and CD44. Through a series of preclinical studies, we showed that fluorophore-based DDSI of EGFR or HER2 provided high tumor-to-normal diagnostic performance, with an area under the curve (AUC) from receiver operator characteristic (ROC) curves routinely > 0.95 [ 35 38 ].…”
Section: Introductionmentioning
confidence: 99%